(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2024)
The article aims to describe the importance of accounting in the management of young people’s personal finances. Starting from a descriptive approach, the main difficulties faced by young people in their financial management due to the lack of accounting training are analyzed. The study generally addresses the need for early financial education. Through a documentary analysis, the educational strategies that could be implemented to facilitate the acquisition of accounting skills from secondary and university education are explored. It is concluded that the incorporation of accounting in educational programs could have a positive impact on the financial stability of young people, improving their decision-making capacity and their economic well-being.